2013
DOI: 10.1111/ced.12213
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice-site mutation in theAAGABgene segregates with hereditary punctate palmoplantar keratoderma and congenital dysplasia of the hip in a large family

Abstract: This observation suggests either the existence of a CDH-associated gene in the vicinity of AAGAB, or a hitherto unrecognized role for p34 during skeletal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Worsening of papules upon exposure to water is a typical feature. 91 Unusual associations, such as familial occurrence of sensorineural hearing loss and ichthyosis vulgaris, 94 congenital hip dysplasia 95 and nail dystrophy, 90 have also been described. Monoallelic mutations have been described in the AAGAB gene encoding for the alpha-and gamma-adaptin-binding protein p34.…”
Section: Other Patterns Of Palmoplantar Keratodermasmentioning
confidence: 99%
“…Worsening of papules upon exposure to water is a typical feature. 91 Unusual associations, such as familial occurrence of sensorineural hearing loss and ichthyosis vulgaris, 94 congenital hip dysplasia 95 and nail dystrophy, 90 have also been described. Monoallelic mutations have been described in the AAGAB gene encoding for the alpha-and gamma-adaptin-binding protein p34.…”
Section: Other Patterns Of Palmoplantar Keratodermasmentioning
confidence: 99%
“…All of these were heterozygous loss-of-function mutations except for one splice-site mutation, c.451 + 1G > A, leading to an in-frame deletion that is expected to result in the loss of 30 amino acids in p34, corresponding to the entire exon 4 in AAGAB [5]. In this study, we reported a novel deletion mutation, c.191_194delCAAA, in exon 2 of the AAGAB gene in two unrelated Japanese pedigrees.…”
mentioning
confidence: 80%
“…To our knowledge, 27 distinct AAGAB mutations were previously reported in familial and sporadic cases of PPPK1, including 11 deletion, nine nonsense, three splice site, three insertion, and one insertion-deletion mutation [1][2][3][4][5][6][7][8]. All of these were heterozygous loss-of-function mutations except for one splice-site mutation, c.451 + 1G > A, leading to an in-frame deletion that is expected to result in the loss of 30 amino acids in p34, corresponding to the entire exon 4 in AAGAB [5].…”
mentioning
confidence: 99%
“…A shorter PCR product was identified, which, when sequenced, showed mutation c.451+3delAAGT resulting in skipping of exon 4 due to deletion of 90 base pairs, resulting in an in‐frame deletion with the loss of 30 amino acids. Interestingly, another mutation at this splice site, c.451+1G>A, has been reported twice, and also results in skipping of exon 4 …”
Section: Mutations and Clinical Details In New Cases Of Punctate Palmmentioning
confidence: 99%